Earth's changing climate - Wolfson, Richard (Chantilly, VA : The Teaching Company, 2007)
In twelve lectures (each 30 minutes in length), Professor Richard Wolfson discusses various aspects of our changing climate
12 lectures delivered by Professor Richard Wolfson, Middlebury College, Vermont
Keywords: Climatic changes; Global warming; Power resources -- Environmental aspects